Sodium trimetaphosphate combined to calcium as a strategy to improve dentin-bonding interface - Gonçalves, Rafael Simões; Speranza Zabeu, Giovanna; Saori Hissano, Wendy; Ciccone Giacomini, Marina; Mendes Cândia Scaffa, Poliana; Rios, Daniela; Marques Honório, Heitor; Wang, Linda (Brazilian Dental Science, 2022)
Objective: The aim of this study was to evaluate the effect of STMP as biomimetic analog of dentin matrix on the dentin bond strength submitted to artificial cariogenic challenge over time. Material and Methods: The total number of teeth used in the experiment was 60 teeth, which were divided into 6 groups (n = 10). Of these total amount, 10 teeth were not submitted to the artificial cariogenic challenge (ACC), serving as control group (Sound Dentin - SD) while the other 50 were submitted to an ACC (7d/37ºC), being treated with treatment solutions according to each group: SD- deionized water/sound dentin, CD- deionized water/ artificial caries dentin, GIIISTMP, GIV- STMP + Ca(OH)2, GV- STMP + NaF, and GVI- NaF. After treatments (24h), the specimens were restored (Adper Single Bond Universal + Filtek Z250), to obtain resin–dentin sticks with a cross sectional area of 0.8mm2, approximately. Two-third of these sticks were stored in artificial saliva (37°C) for analyzes after 6 and 12 months. The 1/3 remains were subjected to mTBS test (baseline). Data were analyzed by two-way ANOVA and Tukey tests (p<0.05). Results: In general, the highest mTBS values were obtained in sound condition (SD), while the artificial caries condition (CD) determined minimum values. Groups treated with NaF (with or without STMP- GV and GVI) were not able to improve adhesion over time. Only the use of STMP + Ca(OH)2 (GIV) improved the mTBS compared to the others caries-challenged dentin after 1 year. The adhesive failure pattern was predominant in all time. Conclusion: The use of the STMP associated with Ca(OH)2 seems to be a viable therapeutic strategy conciliating the biomimetizing capacity to the adhesive process satisfactorily even its performance is not superior to initial condition. KEYWORDS Dentin; Dental adhesive; Protease inhibitors.